The Role of the Social Media and Family Environment on Entrepreneurial Interest of Vocational School Students - Suharto, Suharto; Siswanto, Edy; Ardiyanto, Jefri; Rahayuni, Arintina (Economic Education Analysis Journal, 2022)
The purpose of this study was to analyze the relationship between social media variables on entrepreneurial interest, the relationship between family environment and entrepreneurial interest. This research method is a quantitative survey. Data collection is done by using a questionnaire (likert scale) which is packaged in a google form and distributed through WhatsApp Group. The method in this study is quantitative using the survey method. The study was carried out in August-December 2021 with the research respondents are 188 of vocational School students in Semarang, by using a proportional random sampling technique and using the Slovin formula. Data analysis techniques in quantitative research use structural equation modeling (SEM) and statistical tools SmartPLS 3.3.3 software. The results of the study indicate that there is a positive and significant effect of family environment variables and social media on student entrepreneurship interest. The practical implication of this research is to increase student entrepreneurial interest, so schools must increase social media and family environment variables.